Evaluasi Fungsi dan Kenyamanan Traffic Island Dewa Ruci pada Jalan Bypass Ngurah Rai di Kabupaten Badung - Setiawan, Nahda Sefira; Asmiwyati, I Gusti Agung Ayu Rai; Astiningsih, Anak Agung Made (Jurnal Arsitektur Lansekap; Vol.8, No.1, April 2022DO - 10.24843/JAL.2022.v08.i01.p09, 2022)
Evaluation of Function and Comfortability of Dewa Ruci Traffic Island on Bypass Ngurah Rai Street in Badung Regency. The traffic island is part of an elevated crossroads with curbstone. The main function of the traffic island is as a traffic control and pedestrian safety when crossing. Aesthetically, traffic island has additional function as a landmark and beautification. The Dewa Ruci's traffic island (TIDR) in Badung Regency recently was redesigned for more attractive aesthetical city purpose that has caused activity and traffic violations. Thus, it is necessary to evaluate its function and comfort. The research method used was a survey method with data collection techniques through observation, site documentation, interviews related parties, questionnaires, and literature study. The analysis results showed that the primary function of TIDR which were for traffic control and pedestrian safety were 74,3% and 62,3%, respectively. Its illegal function which was a park area has the highest value (87%). This result also found there were three comfort variables which was low; circulation (50,9%), safety (59,7%), and thermal. Maintenance and management improvement, safety street furniture addition, and rearrangement of pedestrian paths in TIDR were recommended to improve the TIDR comfort.